Capsaicin 8% patch repeat treatment plus standard of care (SOC) versus SOC alone in painful diabetic peripheral neuropathy: a randomised, 52-week, open-label, safety study. Issue 1 (December 2016) - Vinik, Aaron; Perrot, Serge; Vinik, Etta; Pazdera, Ladislav; Jacobs, Hélène; Stoker, Malcolm; Long, Stephen; Snijder, Robert; van der Stoep, Marjolijne; Ortega, Enrique; Katz, Nathaniel
Abstract Background This 52-week study evaluated the long-term safety and tolerability of capsaicin 8% w/w (179 mg) patch repeat treatment plus standard of care (SOC) versus SOC alone in painful diabetic peripheral neuropathy (PDPN). Methods Phase 3, multinational, open-label, randomised, controlled, 52-week safety study, conducted in Europe. Patients were randomised to capsaicin 8% patch repeat treatment (30 or 60 min; 1–7 treatments with ≥ 8-week intervals) to painful areas of the feet plus SOC, or SOC alone. The primary objective was the safety of capsaicin 8% patch repeat treatment (30 min and 60 min applications) plus SOC versus SOC alone over 52 weeks, assessed by changes in Norfolk Quality of Life-Diabetic Neuropathy (QOL-DN) total score from baseline to end of study (EOS). Secondary safety endpoints included Utah Early Neuropathy Scale (UENS) assessments and standardised testing of sensory perception and reflex function. Results Overall, 468 patients were randomised (30 min plus SOC, n = 156; 60 min plus SOC, n = 157; SOC alone, n = 155). By EoS, mean changes in Norfolk QOL-DN total score from baseline [estimated mean difference versus SOC alone; 90% CI for difference] were: 30 min plus SOC, −27.6% [−20.9; −31.7, −10.1]; 60 min plus SOC, −32.8% [−26.1; −36.8, −15.4]; SOC alone, −6.7%. Mean changes [difference versus SOC alone] in UENS total score by EoS versus baseline were: 30 min plus SOC, −2.1 [−0.9; −1.8, 0.1]; 60 min plus SOC, −3.0 [−1.7; −2.7, −0.8]; SOC alone, −1.2. No detrimental deterioration was observed in any of the Norfolk or UENS subscales by EoS with capsaicin. Also, no worsening in sensory perception testing of sharp, warm, cold and vibration stimuli was found with capsaicin by EoS. Capsaicin treatment was well tolerated and the most frequent treatment-emergent adverse events were application site pain (30 min, 28.2%; 60 min, 29.3%), burning sensation (30 min, 9.0%; 60 min, 9.6%) and application site erythema (30 min, 7.7%; 60 min, 8.9%). Conclusion In patients with PDPN, capsaicin 8% patch repeat treatment plus SOC over 52 weeks was well tolerated with no negative functional or neurological effects compared with SOC alone. Trial Registration ClinicalTrials.gov registration:NCT01478607 . Date of registration November 21, 2011; retrospectively registered.